Impact of Donor and Recipient Clinical Characteristics and Hepatic Histology on Steatosis/Fibrosis Following Liver Transplantation. Issue 1 (13th December 2021) - Shaked, Oren; Demetris, Jack; Levitsky, Josh; Feng, Sandy; Loza, Bao-Li; Punch, Jeff; Reyes, Jorge; Klintmalm, Goran; Jackson, Whitney; DesMarais, Michele; Sayre, Peter; Shaked, Abraham; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Deceased donor and recipient predictors of posttransplant steatosis/steatohepatitis and fibrosis are not well known. Our aim was to evaluate the prevalence and assess donor and recipient predictors of steatosis, steatohepatitis, and fibrosis in liver transplantation recipients. Methods: Using the immune tolerance network A-WISH multicenter study (NCT00135694), donor and recipient demographic and clinical features were collected. Liver biopsies were taken from the donor liver at transplant, and from recipients per protocol and for-cause (ie, abnormal transaminases and to rule out rejection) and were interpreted by a central pathologist. Results: One hundred eighty-three paired donor/recipients liver biopsies at the time of transplant and posttransplant follow-up (median time 582 d; average time to last biopsies was 704 d [SD ± 402 d]) were analyzed. Donor steatosis did not influence recipient steatosis or fibrosis. Ten of 183 recipients had steatohepatitis on the last biopsy. Recipient body mass index at the time of liver biopsy was the most influential factor associated with posttransplant steatosis. Both donor and recipient metabolic syndrome features were not associated with graft steatosis. Untreated hepatitis C viral (HCV) infection was the most influential factor associated with the development of allograft fibrosis. Conclusions: In a large experience evaluating paired donor and recipient characteristics, recipient body mass index at the time of liver biopsy was most significantly associated with posttransplant steatosis. Untreated HCV etiology influenced graft fibrosis. Thus relative to untreated HCV, hepatic fibrosis in those with steatosis/steatohepatitis is less common though long-term follow-up is needed to determine the course of posttransplant fibrosis. Emphasis on recipient weight control is essential.